Endoscopic method of intestinal decompression with the use of entero- and colonosorption in treatment of rectal cancer complicated with intestinal obstruction - Kalinin, O.E. (Experimental Oncology, 2013)
The treatment of rectal cancer patients with large bowel obstruction (LBO) is a serious health care problem. That’s why we have studied a possibility of conservative LBO treatment by the method of endoscopic recanalization. Patients and Methods: In the study there have been enrolled 47 rectal cancer patients with acute or partial LBO who were treated with endoscopic recanalization of lumen and following sessions of entero- and colonosorption. After enteric decompression there has been performed preoperative chemoradiotherapy session, and then — planned surgical treatment. Results: Decompression was successful in all 47 patients, however, it’s necessary to note that experimental group has been composed in part from the patients with obstructing rectal tumors with exophytic or mixed growth types. In 5 patients there was a partial effect, and this allowed perform chemoradiotherapy and planned surgical treatment. Conclusion: It has been demonstrated that the use of proposed method of enteric decompression allows quickly eliminate the symptoms of intestinal insufficiency syndrome, perform adequate chemo- and radiotherapy in preoperative period directed on decrease of tumor volume and invasion, facilitate the performance of primary reparative operation and the course of post-operative period, and achieve a decrease number of obstructive resections without worsening the prognosis of the main disease.